Quantification of Lead (Pb), Cadmium (Cd) and Arsenic (As) in Seed of Mucuna pruriens L - thammavong, sonesay; VONGVIXAY , Maiphone; SUVANCHLASY , Sunantha; PHONSAYALINKHAM , Khamla; SINAPHET , Bounmy; KHAMSOUKTHAVONG , Phonepadid (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Mucuna pruriens (M. pruriens) has been utilized in traditional medicine for thousands of years across various Asian countries, including Laos. It is recognized for its significant biological properties, such as strengthening the body and enhancing male sexual fertility. However, ensuring the safety and efficacy of its use is vital, especially regarding potential heavy metal contamination. Heavy metals such as lead (Pb), cadmium (Cd), and arsenic (As) can cause serious health problems, including cancer and Alzheimer’s disease. Thus, contamination in traditional medicines presents a global health risk, particularly when levels exceed WHO guidelines. This study aims to assess heavy metal contamination (Pb, Cd & As) in M. pruriens seeds sourced from nine provinces across three regions of Laos, using Atomic Absorption Spectroscopy (AAS). The results indicate that all samples contained heavy metal levels within WHO limits, with lead concentrations ranging from 0.139 ± 0.08 ppm to 8.818 ± 0.17 ppm and cadmium levels from 0.105 ± 0.02 ppm to 0.211 ± 0.01 ppm. Notably, arsenic was not detected in any of the samples. These findings suggest that the M. pruriens seeds collected from Laos are safe for development into food supplements and for use in traditional medicine.